DOES PHILLIPS CURVE REALLY EXIST? AN EMPIRICAL EVIDENCE FROM JORDAN - Al-zeaud, Hussein; Al-hosban, Saleh (European Scientific Journal, ESJ, 2015)
This study empirically examined the relationship between inflation rate and unemployment rate in order to predict and estimate the existence of Philips curve trade-off relationship within Jordanian economy over the period of 1976 to 2013. It employs multiple descriptive and econometrics approaches using unit root tests, co-integration tests, VECM, and linear and non-linear ordinary least square regression tests. In the findings of this study, there was a negative and non-linear relationship between unemployment and inflation. The lowest limits of inflation and unemployment were estimated to be 3.779% and 11.077% respectively. The elasticity of inflation with respect to unemployment, and the elasticity of unemployment with respect to inflation were estimated to be -0.23% and- 0.02% respectively. Therefore, this study provides a strong empirical existence of Phillips Curve on Jordanian economy over the period of 1976- 2013. However, this trade-off implies that policymakers can target low unemployment or low inflation, but not both. As a result, policy makers should pay attention to this kind of relationship between these two important economic variables in applying fiscal and monetary policies in reducing any of these two variables.